CITES at Forty: Never Too Late to Make Lifestyle Changes. Issue 3 (November 2013) - Couzens, Ed
<x xml:space="preserve">Abstract</x> This article argues that an under‐recognized weakness of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) is that it continues to take the approach of 'categorizing' species, which was the dominant feature of early wildlife‐related conventions such as the 1900 London Convention on the Preservation of Wild Animals, Birds and Fish in Africa. It argues that this approach has in the past been problematic for efforts to protect wildlife and that as long as it continues to be a primary feature of efforts to protect wildlife in the face of modern understandings of the complexities inherent in ecosystems, CITES will never be fully effective. A gradual move toward an (admittedly radical) alternative approach is advocated – at least as far as commercial trade is concerned.